DIGITALISASI PEMBELAJARAN PJOK UNTUK MENINGKATKAN HASIL BELAJAR SENAM AIH - Ramadhan, Javanda Herlyan; Pratama, Dani Slamet; Ratimiasih, Yulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using Canva media in improving learning outcomes of Senam Anak Indonesia Hebat. The research method used was a quantitative method with a Pre-Experimental Design approach, employing a Nonequivalent Control Group Design. The study was conducted at SMAN 1 Tahunan, Jepara Regency. The population consisted of 11 tenth-grade classes. The samples were class X-5 as the experimental class with 36 students and class X-6 as the control class with 36 students. Data collection was carried out using a multiple-choice test consisting of 25 questions. Quantitative data analysis techniques used statistical tests, including prerequisite tests (normality test and homogeneity test) and hypothesis testing using the t-test. The results showed that learning outcomes improved in both classes; however, the improvement in the experimental class was more significant than in the control class. In the control class, the percentage of students in the high category increased from 25% in the pretest to 58.4% in the posttest, while in the experimental class it increased dramatically from 16.7% to 97.2%, with the low category decreasing from 38.9% to 2.8%. Based on the prerequisite tests, the data were normally distributed and homogeneous because all significance values were greater than 0.05 and the Levene’s test result was 0.702 (> 0.05). Furthermore, the t-test result showed a significance value of 0.000 (< 0.05), indicating that H0 was rejected and Ha was accepted. Therefore, it can be concluded that the use of Canva media has a significant effect on improving the learning outcomes of Senam Anak Indonesia Hebat among tenth-grade students at SMAN 1 Tahunan.